751. Karius Cell-Free DNA Metagenomic Assay of Plasma Detects Pulmonary and Disseminated Trichosporon Infections in Patients with Hematological Malignancies. (31st December 2020) - Chen, Tempe; Ahmed, Asim A; Goggin, Kathryn; Wolf, Joshua; Chu, Julie; Pomputius, Bill; Briggs, Benjamin J; Sanacore, Melissa; Solh, Melhem M; Holland, H Kent; Bashey, Asad; Morris, Lawrence; et al.
Abstract: Background: Trichosporon species are uncommon but emerging pathogens that cause life-threatening infections that are resistant to amphotericin B and echinocandins. Diagnosis of deeply invasive trichosporonosis is often elusive to conventional culture methods until locally advanced or disseminated disease has advanced. CT scans Pulmonary Trichosporonosis Lung Bx of Trichosporon detected by Karius Cell-Free DNA Metagenomic Assay of Plasma Methods: Review of cases of next-generation sequencing of microbial cell-free DNA from plasma using the Karius-based technology for establishing a diagnosis of invasive trichosporonosis Results: We found that next-generation sequencing of microbial cell-free DNA from plasma using the Karius-based technology established a diagnosis in six pediatric and adult patients. The median age was 17 yrs (8-72 yrs) all patients had underlying acute leukemia myelogenous leukemia. Six patients had pulmonary nodules and two also had multiple cutaneous lesions with negative blood cultures. Biopsies of one pulmonary nodule and of two cutaneous lesions revealed yeast-like cells. Culture of cutaneous lesions in two patients grew Trichosporon sp. Karius assays performed on plasma and analyzed against a database of more than 300 species of fungi identified Trichosporon asahii in two cases, Trichosporon spp. in three, Trichosporon faecale in one. In all cases, the metagenomic results defined therapy for treatment of invasive trichosporonosis, which is based in antifungal triazoles. In one patient with pulmonary nodules, lung biopsy revealed mixed septate and non-septate hyphal elements that later grew Trichosporon asahii, Rhizomucor pusillus, and Candida parapsilosis, all of which were identified by Karius assay. Conclusion: Invasive Trichosporon spp. are uncommon polyene and triazole-resistant pathogens that cause life-threatening invasive fungal disease resistant in immunocompromised patient with hematological malignancies; next-generation sequencing of fungal cell-free DNA by Karius-based technology identified all six cases of pulmonary and disseminated trichosporonosis, contributing to early detection and pathogen-directed antifungal therapy. Disclosures: Asim A. Ahmed, MD, Karius (Employee) Joshua Wolf, MBBS, PhD, FRACP, Karius inc (Grant/Research Support)